Trauma has an echo: a mixed methods study exploring barriers to routine healthcare for survivors of sexual violence in a UK higher education setting - Jane Meyrick; Laura Hooper (BMJ Open)
Objectives To explore barriers to healthcare among survivors of sexual violence (SV) and the behavioural pathways behind avoidance, focusing on survivor-led solutions.Design A mixed methods study collated qualitative interviews/surveys to explore the lived experiences of survivors of SV. Data were analysed using both quantitative descriptors and qualitative thematic analysis to expand the mechanisms/solutions to reported rates.Setting Higher education setting in the UK.Participants Forty-two survivors of SV between the ages of 18 and 29 self-identified as female (36), male (4), genderfluid (1) and non-binary transmasculine (1), with 10 describing themselves as being from racially minoritised communities and 32 as White survivors.Results Analysis found 86% of survivors completely or significantly avoided healthcare, particularly sexual and reproductive services. Three themes were identified: (1) wider societal blame/marginalisation of survivors hindered their ability to access care in what felt like ‘a system of oppression’; (2) once past these barriers, direct experiences with professionals replicated trauma, exacerbating avoidance and health disparities through ‘healthcare-induced re-traumatisation’; (3) survivors identified what they needed to re-engage in healthcare including trauma-informed professionals and compassionate services with ‘survivor-centred care’.Conclusions SV may deepen health inequalities as survivors avoid healthcare. Survivor-led reforms called for survivor-centred practices and encouraged systemic reflection on how healthcare systems may contribute to the broader marginalisation of survivors. Findings echo policy recommendations for co-produced services led by minoritised/marginalised patients and operationalise trauma-informed training for healthcare professionals. Additionally, access-focused psychological support could reduce the impact of sexual trauma on morbidity and mortality.